Lifestyle: quality of life of the collaborators of a private university - Correa Rodríguez, Egla (2023)
Objective: to determine the index of healthy eating, nutritional status and lifestyle of employees of    a private university. Methodology: non-experimental, analytical, retrospective and cross-sectional design of a population of 88 collaborators from a private university in 2019, applying the Fantástico instrument and the Healthy Eating Index (IAS) and making anthropometric and body composition measurements through the SPSS program version 25. Of the 88 collaborators, 52.3% were women and 47.7% were men, they had a mean age of 41.98 years with an SD 10.388 where the minimum is 23 and the maximum is 82. Results: according to lifestyle, 4 (4.5%) employees had a "somewhat low" lifestyle, 30 (34.1%) employees have an “adequate” lifestyle, 52 (59.1%) employees had a “good job” in their lifestyle and only 2 (2.3%) employees had an “excellent” lifestyle. Regarding the IAS, of the 88 employees, 4 (4.5%) were found in the "unhealthy" category, 72 (81.8%) "need changes" and 12 (13.6%) are “healthy” Conclusion: 72.8% of employees are at risk of contracting chronic degenerative diseases, 53.4% have stage 1 or 2 hypertension, and 86% need changes in their eating habits, which directly infuences quality of life.